EXPLORING THE "PANNUS SIGN ": AN ULTRASONOGRAPHY FINDING FOR DETECTING PLACENTA ACCRETA SPECTRUM AND ITS ASSOCIATION WITH ADVERSE OUTCOMES: A PROSPECTIVE ANALYSIS AT AGA KHAN HOSPITAL, KARACHI - Asra Ahmad; Hussain, Zainab; Bashir, Faryal (Annals of Allied Health Sciences, 2024)
Objective: To evaluate the utility of the sonographic “pannus sign” as an objective marker for identifying PAS in patients, its agreement with histopathology findings, and its association with adverse outcomes. Material & Methods: A 39-months prospective chart review was conducted on patients diagnosed with PAS through ultrasound between March 2020 and June 2023. Demographic, clinical, and imaging data were extracted for analysis. A single researcher recorded the presence or absence of placental pannus on grayscale and color Doppler ultrasound images. The diagnosis of PAS was confirmed through post-cesarean biopsy reports. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated using the chi-square test. Results: The maternal mean age was 32.37±4.31 years, with 64.71% having a cesarean history. The placenta previa was present in 86.30% of the patients. Pannus sign (PS) was positive in 69.60% of the patients, and a diagnosis of a PAS was made in 91.20% via biopsy. PS had a sensitivity of 69.89%, a specificity of 33.33%, a PPV of 91.55%, NPV of 9.68%, and a diagnostic accuracy of 66.67%. Moreover, the relationship between PS and two common surgical procedures, hysterectomy (p=0.534) and bladder repair (p=0.487), revealed no significant link between the two. Conclusion: The pannus sign has moderate sensitivity and specificity but a higher risk of false positives. A positive placental pannus on ultrasound was not associated with hysterectomy or the need for urinary tract repair.